Electrical Bioimpedance Analysis: A New Method in Cervical Cancer Screening. (2nd February 2015) - Das, Lopamudra; Das, Soumen; Chatterjee, Jyotirmoy
Abstract : Cervical cancer is the second most common female cancer worldwide and a disease of concern due to its high rate of incidence of about 500, 000 women annually and is responsible for about 280, 000 deaths in a year. The mortality and morbidity of cervical cancer are reduced through mass screening via Pap smear, but this technique suffers from very high false negativity of around 30% to 40% and hence the sensitivity of this technique is not more than 60%. Electrical bioimpedance study employing cytosensors over a frequency range offers instantaneous and quantitative means to monitor cellular events and is an upcoming technique in real time to classify cells as normal and abnormal ones. This technology is exploited for label-free detection of diseases by identifying and measuring nonbiological parameters of the cell which may carry the disease signature.